Infinite Horizon Incomplete Markets - Magill, Michael; Quinzii, Martine (Econometrica, 1994)
General equilibrium model, Incomplete markets, Speculative bubbles, Short-lived numeraire assets, Pseudoequilibrium, Financial markets